Seismic Performances of SRC Special-Shaped Columns and RC Beam Joints Under Double-Direction Low-Cyclic Reversed Loading - Zhang, Xiangyu; Xia, Qing; Ye, Bailong; Yan, Weiran; Deng, Zhiheng; Xiang, Ping (Frontiers in Materials, 2021)
Steel reinforced concrete (SRC) special shaped column construction is a structural form with good load bearing capacity, ductility and aesthetics. But there is still few experimental and research result relevant to this new structure. The design of SRC special-shaped column joints is a most important problem that must be solved to ensure that this new structural could be widely used in the future. This article focuses the attention on the seismic behavior of this kind of joints, and adopt the new joint design style. The pseudo-static test is carried out on three joints of SRC special-shaped column and reinforced concrete (RC) beam specimens JD-1~JD-3 and one joint of RC special-shaped column specimen JD-4, and then the load-deflection P-Δ，moment-rotation M-ϕ，load-shear deformation P-γ and load-strain hysteresis loop of all the specimens have been drawn. The ductility coefficient μ_Δ and equivalent viscous damping coefficient h_e have been calculated to be contrast with each other, meanwhile, analyze the ductility and capacity of energy dissipating, which possessed important theoretical and applicative purposes. Take into account all these facts，the behavior of high resistant capacity, excellent ductility and reliability of the joint design method have been manifested. Some conclusion derived from this article can be used as a reference to engineering practice.